Multiband optical flux density and polarization microvariability study of optically bright blazars. Issue 1 (18th December 2019) - Pasierb, Magdalena; Goyal, Arti; Ostrowski, Michał; Stawarz, Łukasz; Wiita, Paul J; Gopal-Krishna,; Larionov, Valeri M; Morozova, Daria A; Itoh, Ryosuke; Alicavus, Fahri; Erdem, Ahmet; Joshi, Santosh; et al.
ABSTRACT: We present the results of flux density, spectral index, and polarization intra-night monitoring studies of a sample of eight optically bright blazars, carried out by employing several small to moderate aperture (0.4 to 1.5 m diameter) telescopes fitted with CCDs and polarimeters located in Europe, India, and Japan. The duty cycle of flux variability for the targets is found to be ∼45 per cent, similar to that reported in earlier studies. The computed two-point spectral indices are found to be between 0.65 to 1.87 for our sample, comprised of low- and intermediate-frequency peaked blazars, with one exception: they are also found to be statistically variable for about half the instances where 'confirmed' variability is detected in flux density. In the analysis of the spectral evolution of the targets on hourly time-scale, a counterclockwise loop (soft-lagging) is noted in the flux–spectral index plane on two occasions, and in one case a clear spectral flattening with the decreasing flux is observed. In our data set, we also observe a variety of flux–polarization degree variability patterns, including instances with a relatively straightforward anticorrelation, correlation, or counterclockwise looping. These changes are typically reflected in the flux–polarization angle plane: the anticorrelation between the flux and polarization degree is accompanied by an anticorrelation between the polarization angle and flux, while the counterclockwise flux–PD looping behaviour is accompanied by a clockwise looping in the flux–polarization angle representation. We discuss our findings in the framework of the internal shock scenario for blazar sources.